Phrenic nerve stimulation, a rare complication of pacemaker: A case report - Dalex, Meddy (Medicine (Baltimore), 2021)
RATIONALE: The phrenic nerve stimulation (PNS) is a rare complication after pacemaker setting. We report a case report that describes this complication and how it can be resolved. PATIENT CONCERNS: An 88-year-old man presented himself to the emergency geriatric unit with intermittent painless abdominal contraction due to phrenic nerve stimulation. He has a history of transcatheter aortic valve implantation with cardiac resynchronization therapy pacemaker due to persistent left bundle branch block. DIAGNOSES: All the usual causes for abdominal spasms were eliminated and the possibility of a link with the pacemaker was considered. The phrenic nerve stimulation is a rare complication of a pacemaker implantation. It can be clinically nonrelevant but challenging to diagnose for those not familiar with cardiac devices technology. INTERVENTIONS: Initial setting was an axis of stimulation between distal left ventricular (LV) and right ventricular. It was changed to LV and D1-M2. OUTCOMES: This noninvasive procedure managed to eradicate the involuntary abdominal spasms. LESSONS: PNS could be challenging to diagnose for those not familiar with cardiac devices technology but easy to manage with noninvasive methods.